1999
DOI: 10.1093/emboj/18.11.3024
|View full text |Cite
|
Sign up to set email alerts
|

Serum and glucocorticoid-inducible kinase (SGK) is a target of the PI 3-kinase-stimulated signaling pathway

Abstract: Serum and glucocorticoid-inducible kinase (SGK) is a novel member of the serine/threonine protein kinase family that is transcriptionally regulated. In this study, we have investigated the regulatory mechanisms that control SGK activity. We have established a peptide kinase assay for SGK and present evidence demonstrating that SGK is a component of the phosphoinositide 3 (PI 3)-kinase signaling pathway. Treatment of human embryo kidney 293 cells with insulin, IGF-1 or pervanadate induced a 3-to 12-fold activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
622
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(649 citation statements)
references
References 35 publications
24
622
3
Order By: Relevance
“…SGK1 expression was also highly dependent on IL-6 in INA-6 cells, indicating that SGK1 is a prominent transcriptional target of cytokineinduced signaling in myeloma cells (Supplementary Tables 1b and c; for an overview of SGK1 expression in IH-1, OH-2 and INA-6 cells under different culture conditions see Supplementary Table 1d). As SGK1 exhibits mitogenic and antiapoptotic properties in other cellular systems (Brunet et al, 2001;Leong et al, 2003) and is a component of the PI3K pathway (Kobayashi and Cohen, 1999;Park et al, 1999), which mediates important survival signals for myeloma cells, we decided to analyze the role of SGK1 in MM in more detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SGK1 expression was also highly dependent on IL-6 in INA-6 cells, indicating that SGK1 is a prominent transcriptional target of cytokineinduced signaling in myeloma cells (Supplementary Tables 1b and c; for an overview of SGK1 expression in IH-1, OH-2 and INA-6 cells under different culture conditions see Supplementary Table 1d). As SGK1 exhibits mitogenic and antiapoptotic properties in other cellular systems (Brunet et al, 2001;Leong et al, 2003) and is a component of the PI3K pathway (Kobayashi and Cohen, 1999;Park et al, 1999), which mediates important survival signals for myeloma cells, we decided to analyze the role of SGK1 in MM in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SGK1 protein is regulated at the posttranslational level by phosphorylation and subcellular localization. Similarly to AKT, SGK1 is activated through phosphorylation by phosphoinositide-dependent protein kinase-1 (PDK-1), a signaling intermediate downstream of PI3K (Kobayashi and Cohen, 1999;Park et al, 1999). Several myeloma growth factors, like IGF-1 and HGF, are known to activate the PI3K/AKT pathway, and AKT kinase has been shown to provide important growth and survival signals for MM cells (Tu et al, 2000;Hideshima et al, 2001;Hsu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Mikosz and coworkers concluded that sgk is a survival kinase, as the expression of sgk corre- lates directly with protection against apoptosis in certain cell lines (Mikosz et al 2001). Sgk itself is directly activated by phosphoinositide-3 kinase, and inactivated by PP2A (Park, et al 1999). Although the downstream targets of sgk are unknown, it has been suggested to phosphorylate and inactivate certain transcription factors in the nucleus, which in turn leads to the promotion of cell survival (Brunet et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that the postsynaptically localized I ␀-␣ and NF ␀ act as messenger molecules that travel from the synapse to the nucleus. Serum glucocorticoid kinase (sgk) is another signaling molecule that is transcriptionally regulated by a variety of stimuli including glucocorticoids, p53, and cell injury (Park et al 1999). LSD induced a twofold expression of the sgk gene in all three regions examined around two fold.…”
mentioning
confidence: 99%
“…Sgk1 belongs to a family of serine/threonine kinases that is under acute transcriptional control by serum and glucocorticoids, as well as by an expanding set of hormones, growth factors and cellular stress pathways. 89 Sgk1 is implicated in the regulation of ion channel conductance, cell volume, cell cycle progression and apoptosis. 90 Sgk1 is activated through the phosphatidylinositol 3 kinase (PI3-kinase) pathway by growth factors such as insulin, insulin-like growth factor-1 (IGF1), fibroblast growth factor (FGF), platelet-derived growth factor (PDGF) or tumor growth factor beta (TGF-beta), which activate extracellular signal-regulated kinases (ERKs).…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%